A rizicultura no município de Agudo - RS: uma análise a partir do conceito de rede geográfica - Friedrich, Andréia Carla (2010)
The modern productive relations aim at updating, qualifications and competitiveness towards the competition imposed by the capitalism and the dynamic presented in the production and commercialization relations that, somehow, also influences the agricultural sector imposing new behaviors, patterns and dependencies. This work aims to analyze and discuss the organization of the rice culture in the city of Agudo, RS. In order to do that, the starting point is the conception of a networking area to understand how the integration between sections involved in the production, processing and trade process of rice happens, as well as in the previous steps related to the production process (financing, industry to agriculture, etc.) The methodology used in the development of this work was the collection of data through questionnaires, interviews, informal conversations, photos, statistics and census. Even though the family agriculture is maintained as productive basis, highly dependent of public politics, some sectors of this activity were specialized, maintaining strong relations with each other and assuring its importance in the local market. To make this possible, it was provided a great stimulus through financings and loans, empowering the bonds between growers and processing industries, which broadened their action market through investments in infra-structure and technology. The spatial relations have become more complex when transposing the territories through intersectorial flows.